The Impact of Cloud computing on e-based System: Challenges and Solutions - Praneet Rangi Randhawa, Inderbir Kaur Sandhu, Manisha Malhotra (International Journal of Advanced Science and Technology, 2020)
A systematic implementation of security and privacy parameter of e-health solution on cloud computing is challenging task. The main issue faced by an e-health is secure sharing of healthcare information between medical applications, insurance organization and general practitioner. In order to conquer this challenge, the security of perceptive health information is achieved with encryption and cloud based mechanisms. The Cloud based e-health care system is provides the services to the patients to retrieve the health care information without going to the hospital. This work presents a secured and reliable model for e-health that could promise effectiveness, consistency and organized access approach to health information and also guarantee precise security and privacy among healthcare service providers and the patients.